Preliminary evaluation of a candidate international reference for Epstein–Barr virus capsid antigen immunoglobulin A in China - Hao Chen (Infectious Agents and Cancer, 2020)
Abstract Background The detection of the Epstein–Barr capsid antigen (VCA) immunoglobulin A (IgA) is widely used in the diagnosis of nasopharyngeal carcinoma (NPC), but a reference standard for evaluating the presence of VCA-IgA is not yet available. Therefore, a reference standard is urgently needed for a uniform and quantitative detection of VCA-IgA. Methods A mixed reference serum from three NPC patients diluted with healthy subject serum was made as a potential first international standard for VCA-IgA. VCA-IgA was detected in twenty NPC patients by four ELISA kits and two chemiluminescent immunoassays kits using the reference as a calibration curve. The performance of these six kits was evaluated, and the quantitative results were compared. Results Our results showed a good linearity of the reference in different kits. Without reference, the difference of the total coefficient of variation (from 3.98 to 43.11%) and Within-run coefficient of variation (from 2.47 to 19.66%) was large in the 6 kits. The positive and negative coincidence rate between the 6 kits and indirect immunofluorescence for NPC diagnosis was 75% overall agreement, but a difference among the six kits was found, ranging from 55 to 90%. The concentration of VCA-IgA in the 20 NPC samples led in the division into three categories such as negative, low, or medium/high positive, but these concentrations were significantly different within these three categories depending on the kit used of the 6 considered. However,a good correlation (R2 = 0.986) was observed between Antu and Beier ELISA kits. Conclusions The reference serum mightbe used as a reference standard for a better comparison of the results from different kits/laboratories. However, the quantitative results of some kits are still inconsistent due to the diversity of VCA antigens.